A Utilization-Based Schedulability Test of Real-Time Systems Running on a Multiprocessor Virtual Machine. (14th February 2019) - Niyizamwiyitira, Christine; Lundberg, Lars
Abstract: We consider a real-time application that executes in a VM with multiple virtual cores. Tasks are scheduled globally using fixed-priority scheduling. In order to avoid Dhall's effect, we classify tasks into two priority classes: heavy and light. Heavy tasks have higher priority than light tasks. For light tasks we use rate monotonic priority assignment. We propose a utilization-based schedulability test. If the task set is schedulable, we provide an assignment of priorities to tasks. The input to the test is the task set, the number of cores in the VM, the period, deadline and blocking time for the VM. We evaluate how jitter, when scheduling VMs on the hypervisor level, affects the schedulability of the real-time tasks running in the VM. The schedulability of the real-time tasks in the VM decreases when the hypervisor jitter increases, but on the other hand the schedulability on the hypervisor level increases if we allow more jitter, i.e. there is a trade-off. Our results make it possible to evaluate this trade-off and take informed decisions when selecting scheduling parameters on the hypervisor level. Simulations show that the priority assignment used by our algorithm schedules more task sets than using rate monotonic priority assignment.